Clinical and Radiographic Outcomes of Gap Osteotomy Versus Dorsal Opening Wedge Osteotomy for Extra-Articular Distal Radius Malunion and Internal Fixation Using a Volar Locking Plate Without Bone Graft - Suhas Sondur, MS (Ortho); Anil K. Bhat, MS (Ortho), DNB (Ortho); Shyamasunder Bhat N, MS (Ortho), DNB (Ortho) (Journal of Hand Surgery Global Online)
Purpose: Metaphyseal corrective osteotomy and fixed-angle volar locking plate fixation have reduced the need for additional bone grafting in symptomatic distal radius malunions. This study evaluated the outcomes of gap versus dorsal opening wedge and locking plate fixation without bone grafts for distal radius malunions and the correlation between the osteotomy defect and the osteotomy’s distance from the articular surface with the union time. Methods: We retrospectively reviewed 62 patients who underwent corrective osteotomy between 2010 and 2021. Gap osteotomy (n = 44) was performed to correct the coronal deformity predominantly, whereas an opening wedge osteotomy (n = 18) was performed to correct the sagittal deformity. No bone graft was used in any patient. Radiological outcomes comprised of correction of radial height, inclination, ulnar variance, volar tilt and the correlation between the osteotomy defect and the distance from the distal radial articular surface with the union time. The functional assessment comprised the disabilities of arm, shoulder, and hand questionnaire and the patient-rated wrist evaluation scores. Results: All patients had a union of the osteotomy and statistically significant improvement in the radial height, inclination, ulnar variance, and tilt, irrespective of the osteotomy technique (P < .05). The mean defect length of the osteotomy, the time to the union, and the distance of the osteotomy were 4.7 mm (1–8.3 mm), 11.7 weeks (5–24 weeks), and 13.9 mm (1.6–35.8 mm), respectively. Time taken for union showed a weak positive correlation with the defect length of the osteotomy and no correlation with the distance of the distal osteotomy site from the articular surface. Opening wedge osteotomies took less time than the gap osteotomies. The mean postoperative disabilities of arm, shoulder, and hand questionnaire and the patient-rated wrist evaluation scores were 6.89 and 12.18, respectively. Conclusions: Corrective osteotomy and fixed-angle volar plate fixation for distal radius malunion provide satisfactory union rates and clinical and radiological outcomes even without bone graft, irrespective of the osteotomy type, size, or location. However, length of the osteotomy defect influenced the union time. Type of study/level of evidence: Therapeutic IV.